The Brückner test: extended distance improves sensitivity for ametropia - Gräf, Michael; Jung, Annette (Graefe's archive for clinical and experimental ophthalmology, 2008)
Background The Brückner test is usually performed at a distance of 1 m. Due to optical reasons, the test should detect ametropia more sensitively at an extended distance. We compared the sensitivity of the test to detect unilateral ametropia at a distance of 4 m versus the traditional distance of 1 m. Patients and methods In this study, five blinded experienced observers (experts) performed the Brückner transillumination test on five emmetropic subjects (age 22.3 +/− 2.3 years) at a distance of 1 m which was then extended up to 4 m. Unilateral ametropia was simulated by both spherical and cylindrical lenses of −1, −2, −3, −4, and +1, +2, +3, +4 diopters in front of one eye and a plano lens in front of the other eye in a randomised order. Controls with plano lenses in front of both eyes were interspersed. The test was considered positive in case of any difference between the red reflexes of both eyes. For spherical ametropia, the procedure was repeated with 25 medical students who examined one subject each. Results At a distance of 1 m, unilateral myopia/hypermetropia of more than 1 diopter was detected in 78.7%/71.3% by experts and in 34.7%/53.3% by students. At 4 m, detection rates increased to 99.3%/96.0% and 98.7%/100% respectively. Rates of false positive findings for experts vs students were 3.1% vs 1.5% at 1 m and 4.0% vs 3.0% at 4 m. For unilateral astigmatism, experts’ detection rates were similar at 1 m (64.7%/70.0%) and lower at 4 m (91.7%/90.3%), depending on the astigmatism axis. Conclusions The sensitivity of the Brückner reflex for anisometropia improves by extension of the examination distance, especially in the hands of less experienced observers. To detect ametropia more sensitively, a test distance of 4 m is recommended.